Neuroprotective Effect of the Combination of Citicoline and CoQ10 in a Mouse Model of Ocular Hypertension - José A. Matamoros; Sara Rubio-Casado; José A. Fernández-Albarral; Miguel A. Martínez-López; Elena Salobrar-García; Eva M. Marco; Victor Paleo-García; Rosa de Hoz; Inés López-Cuenca; Lorena Elvira-Hurtado; Lidia Sánchez-Puebla; José M. Ramírez; et al. (Antioxidants)
Glaucoma is a neurodegenerative disease characterized by the loss of retinal ganglion cells (RGCs), with intraocular pressure (IOP) being its primary risk factor. Despite controlling IOP, the neurodegenerative process often continues. Therefore, substances with neuroprotective, antioxidant, and anti-inflammatory properties could protect against RGC death. This study investigated the neuroprotective effects on RGCs and visual pathway neurons of a compound consisting of citicoline and coenzyme Q10 (CoQ10) in a mouse model of unilateral, laser-induced ocular hypertension (OHT). Four groups of mice were used: vehicle group (n = 6), citicoline + CoQ10 group (n = 6), laser–vehicle group (n = 6), and laser–citicoline + CoQ10 group (n = 6). The citicoline + CoQ10 was administered orally once a day starting 15 days before laser treatment, continuing until sacrifice (7 days post-laser). Retinas, the dorsolateral geniculate nucleus (dLGN), the superior colliculus (SC), and the visual cortex (V1) were analyzed. The citicoline + CoQ10 compound used in the laser–citicoline + CoQ10 group demonstrated (1) an ocular hypotensive effect only at 24 h post-laser; (2) prevention of Brn3a+ RGC death in OHT eyes; and (3) no changes in NeuN+ neurons in the dLGN. This study demonstrates that the oral administration of the citicoline + CoQ10 combination may exert a neuroprotective effect against RGC death in an established rodent model of OHT.